2011
DOI: 10.1111/j.1365-2230.2010.03989.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful cutaneous delivery of the photosensitizer silicon phthalocyanine 4 for photodynamic therapy

Abstract: SummaryBackground-Photodynamic therapy (PDT) has been shown to be effective in the treatment of malignancies of a variety of organ systems, including the lungs, bladder, gastrointestinal tract and skin. Cutaneous lesions serve as ideal targets of PDT because of the accessibility of the skin to light. To achieve optimum results, the photosensitizer must be delivered effectively into the target layers of the skin within a practical timeframe, via noninvasive methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The intracellular distribution of Pc 4 within the cervical cancer cells was similar to what has been observed in other tumor cell lines [12,13]. In both cervical cancer cell lines, Pc 4 was localized within the cytoplasm, lysosomes, endoplasmic reticulum and mitochondria.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The intracellular distribution of Pc 4 within the cervical cancer cells was similar to what has been observed in other tumor cell lines [12,13]. In both cervical cancer cell lines, Pc 4 was localized within the cytoplasm, lysosomes, endoplasmic reticulum and mitochondria.…”
Section: Discussionsupporting
confidence: 84%
“…Among Pc 4’s desirable features are: its chemical purity; its high extinction coefficient, 0.23cm −1 μM −1 at 670nm in aqueous solution, a wavelength allowing deep tissue penetration of light; and its rapid clearance from skin which limits the extent and duration of cutaneous photosensitivity after intravenous administration [1012]. Pc 4 PDT induces apoptosis in vitro, due to damage to mitochondria and endoplasmic reticulum [13].…”
Section: Introductionmentioning
confidence: 99%
“…[ 210 ] demonstrated that Pc 4 exhibited less skin photosensititization as compared to Photofrin®. Topically applied, Oleinick and co-workers established that Pc 4 is “effectively delivered into the human skin” [ 211 ] and was consequently investigated clinically. In these trials, Pc 4-mediated PDT was reported to be well tolerated in patients and could have promising application in mycosis fungoides treatment [ 212 ].…”
Section: Phthalocyaninesmentioning
confidence: 99%
“…After hematoporphyrin derivatives have been used as the first approved photosensitizer, various porphyrin derivatives, such as bacteriochlorins, core modified porphyrins, and meso‐tetraaryl porphyrins have been synthesized for PDT application . For example, silicon phthalocyanine has been approved as a PDT photosensitizer for early lung and esophageal cancer in France, the United States, Japan, and Netherlands . Metalloporphyrins with the addition of metals and unique chemical properties present distinct bioinorganic function, which can be used for various biomedical applications, such as PDT, biological stimuli responsive drug delivery, and imaging contrast for positron emission, magnetic resonance, or surface enhanced Raman imaging .…”
Section: Current Organic Dyes For Nanomedicinementioning
confidence: 99%